Perceived internal corporate social responsibility and employees' proactive behavior: The mediating role of intentions to start personal projects and the moderating role of perceived external prestige - Lopéz, A.; Costa, S. (Human Resource Development Quarterly, 2025)
This study deepens our understanding of the micro-level processes underlying the relationship between employees' internal corporate social responsibility (CSR) perceptions (perceived internal CSR) and their proactive behavior. Drawing on the self-regulation and social information processing perspectives, we propose that perceived internal CSR enacts employees' intentions to start personal projects within the organization. We contend that this relationship is contingent upon employees' perceptions of the external prestige of the organization. Additionally, we argue that this interplay influences employees' proactive behavior, specifically innovative and risk-taking actions. Employing a multimethod approach, comprising a multisource field study involving 640 employee-supervisor dyads and a two-by-two experimental design with 152 respondents, our findings demonstrate a positive association between perceived internal CSR and employees' intentions to start personal projects. This effect is stronger when employees perceive the organization as highly prestigious. As predicted, this interaction positively influences innovative and risk-taking behaviors. This research provides valuable insights into the nuanced dynamics between internal CSR and proactive behavior, offering implications for scholars and practitioners in human resource development.